Researching students’ epistemic access under Covid-19: Epistemological and methodological challenges - Cross, Michael; Govender, Logan (Critical Studies in Teaching and Learning, 2023)
This paper aims at critically examining the main epistemological and methodological trends in the scholarship of ‘student access’ and ‘success’ in South African higher education. This is done with reference to key moments in the process of higher education transformation and the main arguments on the individual, social and institutional factors that impact student achievement. The paper considers three intersecting domains: the knowledge foundational domain, the social domain, and the research discursive domain. It explores how these domains interface with the individual agency of the researcher and the participant with reference to the imagery and imaginary constructed around difference. The paper shows how the analytical discourses of access have largely reflected global theoretical influences which do not always speak to the local context. Thus, the paper calls for de-colonial approaches rooted in epistemic justice that account for the contextual peculiarities of student agency and experience.